Analyzing the Competitors of Stock Market for Stock Investments (A Study on Textile Industry under Dhaka Stock Exchange, Bangladesh) (Global Journal of Management and Business Research, 2019)
The stock market refers to the collection of markets and exchanges where buying and selling of shares of publicly held companies takes place. Here in this paper we mainly focus on Dhaka Stock Exchange. Where we choose the Textile Industry listed in Dhaka Stock Exchange for analyzing the competitors. As the Textile Industry of Bangladesh is a successful industry so competitor analysis is important issue to consider. Here we supposed to hold the shares of HR. Textile Ltd and we also take another six textiles to analyze the competitors. By the competitor analysis we can ensure whether to hold the current company shares or we should switch the company.
Keywords: stock exchange; stock market; stock; earning per share; dividend